Studi Pengaruh Kemudahan Akses Aplikasi dan Kualitas Layanan terhadap Kepuasan Pelanggan Shopee Food - Ani Nuriska Safitri; Mawalda Azharah; Khiyarana Fayziyah; Nadia Septia Aisyah; Antonius Yadi kuntoro; Riza Fahlapi; Dedi Dwi Saputra; Hermanto Hermanto; Taufik Asra (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
The development of information and communication technology in Indonesia has driven the rapid growth of app-based food delivery services, such as ShopeeFood. The ease of using the application and the quality of service are key factors influencing user satisfaction in utilizing this service. This study aims to analyze the influence of application ease of use and service quality on ShopeeFood user satisfaction in Depok. A quantitative approach was used, with primary data collected through questionnaires distributed to 100 respondents. The data was processed using SPSS by conducting data quality tests, classical assumption tests, t-tests, and F-tests. Based on the research findings, it was concluded that both application ease of use and service quality have a significant influence on user satisfaction, both individually (partially) and jointly (simultaneously). The t-value for ease of use was 6.576 and for service quality was 4.929, both exceeding the t-table value of 1.984 with a significance level of 0.000. Simultaneously, the F-value of 37.967 also indicates a significant influence.